A fatal outcome in a patient with coeliac disease who suspended a strict gluten-free diet: a case report. Issue 12 (December 2021) - Lu, Chong; Zheng, Xiao-Juan; Hua, Hong-Jun; Wang, Qun-Ying
Coeliac disease (CD) is an autoimmune small bowel disease that occurs in susceptible individuals that develop an immunological reaction to gluten. A strict gluten-free diet (GFD) is the primary treatment for CD. This case report describes a patient with CD recurrence due to a discontinuation of a strict GFD by the patient. After recurrence, the patient developed fever and pancytopaenia, and quickly died of haemophagocytic lymphohistiocytosis (HLH). To the best of our knowledge, this is the first description of a case of CD associated with HLH due to discontinued GFD, which may contribute to improving the awareness of the importance of maintaining a strict GFD and having regular follow-up examinations.